2022
DOI: 10.3390/cryst12060804
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength Enhancement in Early Age Acid Activated Mortars: Mechanical Properties and Analysis

Abstract: To increase the hydration reaction rate and the amount of hydration products, different types and proportions of acids were mixed into mortars. The effects of the acid type and content on the early compressive strength of cement-based materials and the strengthening mechanism were assessed via X-ray diffraction and Fourier-transform infrared spectrum analyses. The addition of acetic acid or hydrochloric acid significantly increased the compressive strength of mortars at 1 d and 3 d, and slightly increased it a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This shows that the addition of GBFS to PC could not promote the hydration reaction and accelerate the formation of hydration products [ 29 ]. It merely played the role of inert filling and GBFS could not fully utilize its reactivity in the PC-based environment [ 30 ]. Therefore, the compressive strength of PC grouting material followed a clear decreasing trend with an increase in GBFS content.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the addition of GBFS to PC could not promote the hydration reaction and accelerate the formation of hydration products [ 29 ]. It merely played the role of inert filling and GBFS could not fully utilize its reactivity in the PC-based environment [ 30 ]. Therefore, the compressive strength of PC grouting material followed a clear decreasing trend with an increase in GBFS content.…”
Section: Resultsmentioning
confidence: 99%
“…Many particles that do not participate in the polymerization remain scattered on the surface of sample C-7. This indicates that the addition of a foaming agent severely affected both the polymerization and the formation of polymerization products, severely influencing the mechanical properties [ 42 ]. Moreover, many micron-grade severely harmful pores present a disordered distribution on the surface of sample C-7 and penetrate the sample, forming a penetration defect and destroying the overall structure.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous research studies have shown promising results, the dependence on PC has not been surpassed [16,17]. Moreover, utilizing only a single material, i.e., coal gangue or fly ash, as the filling material cannot fully utilize various solid wastes [18,19].…”
Section: Introductionmentioning
confidence: 99%